Selective oxygenation of C-H and CC bonds with H 2 O 2 by high-spin cobalt(II)-carboxylate complexes - Ghosh, Ivy; Chakraborty, Biswarup; Bera, Abhijit; Paul, Satadal; Paine, Tapan Kanti (Dalton transactions : an international journal of inorganic chemistry, 2022)
Four cobalt(II)-carboxylate complexes [(6-Me -TPA)Co (benzoate)](BPh ) (1), [(6-Me -TPA)Co (benzilate)](ClO ) (2), [(6-Me -TPA)Co (mandelate)](BPh ) (3), and [(6-Me -TPA)Co (MPA)](BPh ) (4) (HMPA = 2-methoxy-2-phenylacetic acid) of the 6-Me -TPA (tris((6-methylpyridin-2-yl)methyl)amine) ligand were isolated to investigate their ability in H O -dependent selective oxygenation of C-H and CC bonds. All six-coordinate complexes contain a high-spin cobalt(II) center. While the cobalt(II) complexes are inert toward dioxygen, each of these complexes reacts readily with hydrogen peroxide to form a diamagnetic cobalt(III) species, which decays with time leading to the oxidation of the methyl groups on the pyridine rings of the supporting ligand. Intramolecular ligand oxidation by the cobalt-based oxidant is partially inhibited in the presence of external substrates, and the substrates are converted to their corresponding oxidized products. Kinetic studies and labelling experiments indicate the involvement of a metal-based oxidant in affecting the chemo- and stereo-selective catalytic oxygenation of aliphatic C-H bonds and epoxidation of alkenes. An electrophilic cobalt-oxygen species that exhibits a kinetic isotope effect (KIE) value of 5.3 in toluene oxidation by 1 is proposed as the active oxidant. Among the complexes, the cobalt(II)-benzoate (1) and cobalt(II)-MPA (4) complexes display better catalytic activity compared to their α-hydroxy analogues (2 and 3). Catalytic studies with the cobalt(II)-acetonitrile complex [(6-Me -TPA)Co (CH CN) ](ClO ) (5) in the presence and absence of externally added benzoate support the role of the carboxylate co-ligand in oxidation reactions. The proposed catalytic reaction involves a carboxylate-bridged dicobalt complex in the activation of H O followed by the oxidation of substrates by a metal-based oxidant.